A Production and Operations Management study on Alliance Global Inc. - Del Rosario, Francis Edward N. (College of Engineering, 2001)
Alliance Global Inc. is a Laguna-based company specializing in the production of flint bottles. Their product is composed of several components, such as cullets, silica sand, soda ash, limestone, and other minor constituents. The processes involved in making these bottles are: batch preparation, melting, forming, annealing, inspecting and packaging where most of the processes are automated and synchronized. Thus, the effective capacities of these processes are equal. The number of workers and the manual operations (inspection and packaging) however, is adjusted to maintain system balance. Using streamline analysis and cause and effect diagrams, the group determined four major problems regarding the company's production system, namely, (1) Errors in Forecasting, (2) Inefficient Workforce Plan, (3) Poor Facility Layout, and (4) Wrong Inventory System. The group then proposed and evaluated several alternatives for each problem. Under forecasting, the several quantitative forecasting techniques were evaluated to determine the most appropriate forecasting model. In the second problem, the group compared a two-shift and three-shift plan. Regarding poor facility layout, the group proposed redesigning the layout, including devising a warehouse plan for systematic retrieval and a fee for late pick-ups of orders. And for the last problem, the group suggested three inventory systems as possible alternatives: (1) MRP, (2) Q system and (3) P System. After much analysis, the group recommended the following for each problem: The Exponential Smoothing Model (alpha=0.05) is the most appropriate forecasting model because it yielded the lowest tracking signal. From the chosen alpha, tow forecasts are made for the year 2001. One was in kilograms, which is used to determine future demand and for raw materials management, while the order forecast is in units of bottles which is used to determine workforce level. For the workforce plan, the group suggested that it would be more beneficial to the company to implement a 3-shift workforce plan because this plan would give the company less daily wage costs. IT was also suggested that organization in the storage facilities layout would include the redesign of the storage facilities by using the proposed warehouse layout and the implementation of a fee for late pick-ups to reduce the crowded storage areas. Finally the group also suggested that the Q system ( fixed order quantity) as the appropriate inventory system for the company. This system would minimize wastage of raw materials and at the same time generate the least inventory costs.